Influence of Talent Management and Organisational Performance on Employee Retention among First Bank Employees in Osogbo, Osun State - Ojo, Solomon; Alli, Olumide Muktar (Quest Journal of Management and Social Sciences, 2024)
Background: This study investigated the influence of talent management and organisational performance on Employee Retention in First Bank Plc, Osun State, Nigeria. Objectives: The study was meant to achieve the following objectives: assess the influence of talent management on employee retention among employees of First Bank Plc, Osun State, Nigeria; determine the influence of organisational performance on employee retention among employees; assess the influence of talent planning on employee retention among employees; investigate the influence of workplace culture on employee retention among employees; assess the influence of talent recruitment and retention on employee retention among employees; determine the influence of talent development on employee retention among employees; investigate the influence of talent development on employee retention among employees; determine the influence of professional advancement and rewarding the employees on employee retention. Methods: The study was a survey in which an Ex-post facto design was employed. A total of 100 bank employees took part in the study. A questionnaire format was used to collect data in the study. Collected data were subjected to both Descriptive and Inferential statistics, with the adoption of Statistical Package for Social Sciences. Results: The results revealed there was a significant influence of talent management on employee retention in First Bank Plc [t(98)=6.73, p<.01]; there was a significant influence of organisational performance on employee retention in First Bank Plc [t(98)=8.65, p<.01]; there was a significant influence of talent planning on employee retention in First Bank Plc [t (98)=4.15, p<.01]; there was a significant influence of workplace culture on employee retention in First Bank Plc [t(98)=3.74, p<.01]; there was a significant influence of talent recruitment on employee retention in First Bank Plc [t (98) =3.75, p<.01]; there was a significant influence of talent development on employee retention in First Bank Plc [t (98) =8.87, p<.01]. Conclusion: Hence, it is concluded that talent management and organisational performance significantly influence employee retention. It was recommended that management teams of Banks ensure that outstanding performance is awarded in the organisations, and employee participation and engagement should be emphasised for talent management to be successfully implemented.